Rethinking Venice from an Ecosystem Services Perspective - Jane da Mosto; Camilla Bertolini; Anil Markandya; Paulo A.L.D. Nunes; Tom Spencer; Arnas Palaima; Laura Onofri (Fondazione Eni Enrico Mattei (FEEM), 2020)
Safeguarding the future of Venice is a globally recognised challenge of urban sustainability. We propose a sustainable management model, alternative to the current strategy, that primarily focuses on the built heritage and which interprets the city together with its encircling lagoon as a matrix of interlinked natural, cultural and social capital. In particular, Venetian natural capital can be valued as a stock of wealth that produces a flow of income, its ecosystem services. Such values can be measured in economic, including monetary, terms. Using the examples of salt marsh and seagrass carbon sequestration, together with sediment retention, water purification and artisanal fishery and aquaculture, we show that it is economically viable to develop and reorientate the nearfuture trajectory of Venice and its lagoon with reference to a more sustainable pathway, where the natural capital is a driver of future economic development and, as such, is comparable with the value of currently dominant economic activities (port and mass tourism).
Keywords: Q56; Q57; R58; 330; Natural Capital; Ecosystem Services; Eecosystem Services Economic Valuation; Sustainability; Venice Lagoon; Alternative Management Strategies